Chinese experience on using RWE to support drug research, development and evaluation - A. S. Kolbin; D. Yu. Belousov (Реальная клиническая практика: данные и доказательства, 2022)
The article describes the regulatory approaches to the collection, analysis and usage of real-world data applied in China.